Pureza [motion picture] the story of Negros sugar - Abello, J.; Borres, Fiona; National Commission for Culture and the Arts. (Philippines Negros Pureza and Bonfire Productions, Inc., 2012)
No Sugar coating. Pureza: The sotry is Negros Sugar is a full-lenght documentary film on the struggling sugar industry of the island of Negros in the Philippines and how a piece of cryatallized grain could affect a whole island of 2.7 million people.
At turn of the 20th century, Negrense hacienderos (sugarcane land owners) were the richest and their farm workers the highest paid in the country. But in a span of a century, the Negros sugar industry plunged from its proverbial pedestal into its inglrious present state.
Filmmaker J. Abello, a former sugarcane farm manager, offers a glimpse of the island's turbulent history through dramatic and contorversial video: lavish parties of Negros sugar baron's, candid inteviews with hacienderos, never before seen footage of Negros island ... and more.
When the sugar industry sneezes, the islnad gets a cold.
PG 13
Producers: Fiona Borres, Agnes Villar; Executive Producers, J. Abello, Joey Gaston
Keywords: Sugar Industry -- Negros -- Documentary